The dysregulation of metabolic pathways and induction of the pentose phosphate pathway in renal ischaemia–reperfusion injury - Scantlebery, Angelique ML; Tammaro, Alessandra; Mills, James D; Rampanelli, Elena; Kors, Lotte; Teske, Gwendoline J; Butter, Loes M; Liebisch, Gerhard; Schmitz, Gerd; Florquin, Sandrine; Leemans, Jaklien C; Roelofs, Joris JTH (The Journal of pathology, 2021)
Lipid accumulation is associated with various forms of acute renal injury; however, the causative factors and pathways underpinning this lipid accumulation have not been thoroughly investigated. In this study, we performed lipidomic profiling of renal tissue following ischaemia–reperfusion injury (IRI). We identified a significant accumulation of cholesterol and specific phospholipids and sphingolipids in kidneys 24 h after IRI. In light of these findings, we hypothesised that pathways involved in lipid metabolism may also be altered. Through the analysis of published microarray data, generated from sham and ischaemic kidneys, we identified nephron‐specific metabolic pathways affected by IRI and validated these findings in ischaemic renal tissue. In silico analysis revealed the downregulation of several energy and lipid metabolism pathways, including mitochondrial fatty acid beta‐oxidation (FAO), peroxisomal lipid metabolism, fatty acid (FA) metabolism, and glycolysis. The pentose phosphate pathway (PPP), which is fuelled by glycolysis, was the only metabolic pathway that was upregulated 24 h following IRI. In this study, we describe the effect of renal IRI on metabolic pathways and how this contributes to lipid accumulation. © 2020 The Authors. The Journal of Pathology published by John Wiley & Sons, Ltd. on behalf of The Pathological Society of Great Britain and Ireland.